Nutritional Counseling of Stroke Patients by Neurology Residents, a Call to Action - Benameur, Karima; Gandrakota, Nikhila; Ali, Mohammed K. (Frontiers in Neurology, 2022)
Background: Poor diet quality has been found to be an independent risk factor for mortality in stroke. However, it is unknown to what extent Neurologists are trained and are comfortable enough to provide dietary counseling to stroke patients. Objective: To assess the knowledge, attitudes, and practices of neurology residents relating to dietary counseling of stroke patients. Methods: An online anonymous survey was administered to neurology residents throughout the country between August and November 2019 among a total of 109 (68%) US neurology programs. Self-reported practices and knowledge regarding stroke prevention through nutritional counseling were queried using validated questionnaires. Results: 453 responses out of a potential 672 were received. A minority of residents (12.3%) consistently offered nutritional counseling to stroke patients. 47.7% considered that it was not the neurologist’s role to provide nutritional counseling to stroke patients. 83.4% of residents felt that it was the responsibility of the dietician to provide nutritional counseling, yet only 21.4% of residents consistently referred stroke patients to a dietician. 77.9% of respondents felt nutritional counseling is important for stroke patients, yet 65.6% felt they were not adequately trained to provide nutritional counseling. Conclusion: Neurologists in training believe diet to be an important part of stroke prevention, but practical knowledge and training in nutrition are suboptimal. This study suggests the need to include nutrition as an integral part of neurology training, to ensure neurologists feel empowered to be an important part of the team providing nutritional counseling to stroke patients.